(untitled) - Anspaugh, David J. (Boston, 2003)
Incorporating updated material, this edition emphasizes a proactive, balanced body/mind/spirit approach to health and fitness. The introductory textbook includes self-assessments, a nutritional analysis of foods from selected fast-food restaurants, the latest USDA food guide, a self-care guide for common ailments, and color graphics. An auxiliary online learning resource is available. Dates are not given for previous iterations. Anspaugh teaches at Tri-State U. in Indiana
Keywords: Health,Self-care, health,Medicine, preventive